(untitled) (Research, Society and Development, 2022)
Objective: Sebaceomas are benign lesions but they can be associated with cutaneous and internal malignancies and, thus, may not have a good prognosis, as when associated with the Muir-Torre Syndrome (MTS). Methodology: This is a clinical case report aimed at describing and discussing the case presented. Description of the case: The case in question presents a female patient aged 45 years old, with a fibroelastic and yellowish 0.3 cm papule in the malar region for nearly 5 years, without any other associated symptoms or dermatoscopic criteria specific to the dermatological exam. The following diagnostic hypotheses were made at first instance: sebaceous hyperplasia, sebaceous cyst or epidermal cyst. The choice was to perform surgical exeresis of the lesion due to the aesthetic inconvenience it generated to the patient. The anatomopathological study showed presence of roundish and juxtaposed cell blocks with sebaceous differentiation; peripherally consisting of basaloid cells, in addition to polyhedral neoplastic cells, large and with indistinct and scarce cytoplasm, in addition to voluminous nuclei with mild to moderate pleomorphism, coarse vesicular chromatin and frequent mitosis. In the immunohistochemistry test, there was adipophilin expression in the sebaceous cells, with a microgoticular pattern, in addition to diffuse positivity for protein p63. Consequently, a sebaceoma diagnosis was made. Conclusion: This case made us reflect about the difficulty regarding clinical and dermatoscopic differentiation of sebaceous tumors; it also shows the importance of the need to pay attention to the possibility of an association between sebaceoma and the Muir-Torre Syndrome, which can alter the patient’s prognosis. In the case in question, there were no specific clinical criteria that made us raise that diagnostic possibility.